PENGARUH PEMERDAYAAN MASYARAKAT NELAYAN TERHADAP TINGKAT PENDAPATAN NELAYAN DI KELURAHAN KAREKON KECAMATAN LEMBEH UTARA KOTA BITUNG - DARENO, RALDY; LENGKONG, FLORENCE; PLANGITEN, NOVVA (Sam Ratulangi University, 2019)
Empowerment of fishing communities is an activity that involves the participation of empowered fishing communities. Empowerment of fishing communities is a concept developed to strengthen the independence of fishing communities. Where the empowerment of fishing communities includes increasing knowledge and abilities of fishermen, through socialization and training, development, supervision, communication and coordination and guidance through support, through motivation and provision of facilities. For that, theres need more attention from the government concerned to conduct and carry out empowerment programs for fishing communities where the aim is to make fishing communities better informed, competent and have good abilities so that their income increases. This study uses a type of quantitative research, namely research that analyzes data statistically with the aim to determine the effect of variable community empowerment on income variables. Data collection is done by distributing questionnaires to 65 fishermen communities that have been determined, then the data is processed using statistical methods using the SPSS version 20. The results of simple regression analysis are known to know that the constant value (a) is 15,734 while the value (b or coefficient Regression) obtained a positive value of 0.369 so that the regression equation can be written Å¶ = 15.734 + 0.369X. Where every 1% increase in the value of Community Empowerment, the income value increases by 0.369 or 36.9%, so it can be concluded that the direction of the variable community empowerment (X) on the income variable (Y) is positive. Community Empowerment has a significant effect on Income Levels.Keywords: Community Empowerment, Fishermen, Income.